Предмет: Математика,
автор: БешенаяСгущёнка2015
Решите уравнение:(2x-3)*(3x+2)-(x-1)+(5x+2)*(x-14) заранее СПАСИБО
Ответы
Автор ответа:
0
6x^2 + 4x - 9x - 6 - x - 1 + 5 x^2 - 70 + 2x - 28
6x^2 + 4x - 9x - x + 5x^2 + 2x = 6 + 70 + 28 +1
11 x^2 - 4x = 105
11x2 - 4x - 105 = 0
Так?
6x^2 + 4x - 9x - x + 5x^2 + 2x = 6 + 70 + 28 +1
11 x^2 - 4x = 105
11x2 - 4x - 105 = 0
Так?
Автор ответа:
0
Да огромное спасибо все верно!
Похожие вопросы
Предмет: Физика,
автор: maks2008prihodko
Предмет: Қазақ тiлi,
автор: jusaihu
Предмет: Английский язык,
автор: Аноним
Предмет: Математика,
автор: Aneka00